Aportaciones a la flora del sur de Galicia (NO España) - Pulgar Sañudo, Ínigo (Botanica Complutensis, 2006)
Eight new appointments of vascular plants (seven indigenous and one alien) are presented in the provinces of Ourense and Pontevedra (Galicia, Spain). Two of them constitutes novelty for the Spanish flora (Galium belizianum and Hakeasericea), five more they constitute new appointments of Ourense province (Centaurea debeauxii, Lythrum borysthenicum, Pterospartum tridentatum subsp. lasianthum, Thymus serpyllum subsp. caroli and Trifolium occidentale), and two more are new for the province of Pontevedra (Dianthus laricifolius subsp. merinoi, and Pterospartum tridentatum subsp. cantabricum). It is confirmed the presence of Heracleum sphondyllium subsp. granatense in the province of Ourense.